The role of the molecular weight of polyvinylpyrrolidone in the formation of two-layer polyamide/hydrogel membranes of increased strength - Баран, Н. М.; Гриценко, Т. О.; Дулебова, Л.; Baran, N. M.; Grytsenko, T. O.; Dulebova, L. (Lviv Politechnic Publishing House, 2023)
Наведено результати дослідження впливу молекулярної маси полівінілпіролідону на властивості двошарових гідрогель/полікапроамідних мембран. Композиційні мембрани одержано розробленим методом, який полягає у формуванні гідрогелевих мембран з подальшим осадженням з розчину в їх зовнішню поверхню зміцнювального шару на основі поліаміду, модифікованого полівінілпіролідоном. Встановлено, що молекулярна маса полівінілпіролідону, як у складі гідрогелевої мембрани, так і в модифікувальному розчині, істотно впливає на взаємодію між шарами композиційних мембран та їх характеристики, такі як водовміст, міцність під час проривання, осмотичну солепроникність.

The article presents the results of a study of the influence of the molecular weight of polyvinylpyrrolidone on the properties of two-layer hydrogel/polycaproamide membranes. Composite membranes are obtained by the developed method, which consists in the formation of hydrogel membranes with subsequent deposition from a solution into their outer surface of a reinforcing layer based on polyamide modified with polyvinylpyrrolidone. It was established that the molecular weight of polyvinylpyrrolidone, both in the composition of the hydrogel membrane and in the modifying solution, has a significant effect on the interaction between the layers of composite membranes and their characteristics, such as water content, bursting strength , and osmotic salt permeability.
Роль молекулярної маси полівінілпіролідону у формуванні двошарових поліамід/гідрогелевих мембран підвищеної міцност
Keywords: двошарові мембрани; молекулярна маса; гідрогель; 2-гідроксіетилметакрилат; полівінілпіролідон; поліамід; two-layer membranes; molecular weight; hydrogel; 2-hydroxyethyl methacrylate; polyvinylpyrrolidone; polyamide